Improvement of System Thinking Skills on Excretory System Subject - Noviyani Rachmat; Tri Wahyu Agutina; Asrianty Mas’ud (Jurnal Report of Biological Education, 2023)
Background: System thinking skills are a learning process that improves system thinking or systematic thinking in students. The purpose of this study was to determine the increase in Systems Thinking Skills (KBS) by using the Guided Inquiry Learning Model on Human Excretion System Material for class XII MIPA students in a school in Subang. Methods: This research method uses quantitative research with a quasy experimental design. Results: The results of the analysis of the increase or N-gain obtained by system thinking skills (KBS) using the guided inquiry model show that there are five categories of high system thinking skills (KBS) indicators, namely the fourth indicator analyzes disorders of the excretory system organs of 0.5472, and the indicator that the lowest, namely the second indicator examines the four functions of the excretory system of 0.0220. Conclusion: Thus it can be concluded that there is a positive influence of the Guided Inquiry Learning Model on Systems Thinking Skills (KBS) in Excretion System Material for Class XI MIPA Students in Subang Regency. Keywords : Guided Inquiry; Systems Thinking Skills; Learning model